2000
DOI: 10.1002/1097-0282(200011)54:6<448::aid-bip80>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A model for type II collagen fibrils: Distinctive D‐band patterns in native and reconstituted fibrils compared with sequence data for helix and telopeptide domains

Abstract: The periodical D-band pattern is generally considered a unique ultrastructural feature shared by all fibril-forming collagens, which correlates with the intrafibril, paracrystalline array of tropocollagen monomers. Distinct band patterns have been reported, however, for collagen stained long-spacing (SLS) crystallites of genetic types I, II, and III. Moreover, D-band patterns of negatively stained, native type II collagen fibrils were found to be not identical to those of type I in our previous research. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…In contrast, the proposed collagen type II C-telopeptide structure is much closer to that observed for the collagen type I C-telopeptide and to the prediction of Ortolani et al (39). It has tyrosine (Tyr-1058) and methionine (Met-1055) residues at the end that have been moved deeper into the overlap region, closer to the N terminus.…”
Section: Experimental and Model Electron Density Maps Of The Type II supporting
confidence: 83%
See 4 more Smart Citations
“…In contrast, the proposed collagen type II C-telopeptide structure is much closer to that observed for the collagen type I C-telopeptide and to the prediction of Ortolani et al (39). It has tyrosine (Tyr-1058) and methionine (Met-1055) residues at the end that have been moved deeper into the overlap region, closer to the N terminus.…”
Section: Experimental and Model Electron Density Maps Of The Type II supporting
confidence: 83%
“…Electron microscopy studies of human collagen type II fibers suggested that the folding of the telopeptides is similar to that proposed here (39), but the 20 nm resolution of those studies was not sufficient to provide conclusive evidence (the stretched N-and C-telopeptides are 4.5 nm and 5.4 nm in length, respectively). Similarly, studies with synthetic or ex vivo collagen N-and C-telopeptides indicated an axial compression of the fragment(s), with possible folding (52-54).…”
Section: Experimental and Model Electron Density Maps Of The Type II mentioning
confidence: 73%
See 3 more Smart Citations